2010
DOI: 10.1002/eji.200939646
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of lipid rafts in CD154‐mediated T cell signaling

Abstract: Although signal pathways triggered via the CD40 molecule are well characterized, those induced via CD154 are less known. This study demonstrates that engagement of CD154 in Jurkat D1.1 cells with soluble CD40 leads to PKC a and d activation, calcium mobilization, and phosphorylation of the Map kinases ERK1/2 and p38. Such response is accompanied by significant recruitment of CD154 into lipid rafts. Disruption of lipid rafts integrity with nystatin or methyl b-cyclodextrin abrogated PKCa PKCd and p38 phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 49 publications
(75 reference statements)
3
21
0
Order By: Relevance
“…1C). Taken together, these results confirm our previously reported data demonstrating a translocation of CD154 into lipid rafts upon its stimulation [15], indicate that such translocation does not involve its cytoplasmic domain and does not therefore require CD154 intracellular signaling.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1C). Taken together, these results confirm our previously reported data demonstrating a translocation of CD154 into lipid rafts upon its stimulation [15], indicate that such translocation does not involve its cytoplasmic domain and does not therefore require CD154 intracellular signaling.…”
Section: Resultssupporting
confidence: 92%
“…We have previously demonstrated that stimulating CD154 induced IL-2 production in T cells co-stimulated at their T cell receptor (TCR) [15]. Therefore, we aimed herein at investigating the role of lipid rafts in CD154-induced IL-2 production using T cells transfected with wild type or chimeric forms of CD154.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-CD40 monoclonal antibody (clone G28.5) was purified from hybridoma cell lines as outlined previously (15). Human soluble CD40-Fc was generated in our laboratory as described previously (16). Mouse and human IgGs (isotype controls) were purchased from Santa Cruz Biotechnology.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that CD154-mediated signaling in T cells acts as a co-stimulator to enhance T cell activation. 36 As the expression profiles of CD40 and CD154 are different, 17 and CD154 can function through distinct receptors additional to CD40, such as Mac-1/CD11b, 37 it is possible that the distinct phenotypes observed may result from overlapping but different physiologic alterations in mice lacking CD154 vs. CD40. More studies are required to delineate the specific roles of CD154 and CD40 in metabolic disease.…”
Section: The Role Of Cd40 In Obesity and Irmentioning
confidence: 99%